RESOURCE FACTORS THAT INFLUENCE THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS IN COOPERATIVES - I Gusti Ayu Asri Pramesti; I Dewa Made Endiana; I Wayan Wahyu Kharisma (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2023)
ABSTRACTThis study aims to determine the influence of training and education, competence, utilization of information technology, speed of accounting information systems, and top management support on the effectiveness of accounting information systems in savings and loan cooperatives in the Sukawati District. The population of this study was all employees of a savings and loan cooperative in Sukawati District. The sampling method used is purposive sampling. The respondents from this study were 72 respondents. The analysis technique used in this study is multiple linear regression analysis. The results of this study show that the speed of the accounting information system has a positive effect on the effectiveness of the accounting information system, while training and education, competence, utilization of information technology, and top management support do not affect the effectiveness of the accounting information system.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh pelatihan dan pendidikan, kompetensi, pemanfaatan teknologi informasi, kecepatan sistem informasi akuntansi dan dukungan manajemen puncak terhadap efektivitas sistem informasi akuntansi pada koperasi simpan pinjam di Kecamatan Sukawati. Populasi dari penelitian ini adalah seluruh karyawan koperasi simpan pinjam di Kecamatan Sukawati. Metode sampling yang digunakan adalah purposive sampling. Responden dari penelitian ini sebanyak 72 responden. Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi linear berganda. Hasil Penelitian ini menunjukkan bahwa kecepatan sistem informasi akuntansi berpengaruh positif terhadap efektivitas sistem informasi akuntansi, sedangkan pelatihan dan Pendidikan, kompetensi, pemanfaatan teknologi informasi serta dukungan manajemen puncak tidak berpengaruh terhadap efektivitas sistem informasi akuntansi.